Markerless Analysis of Gait Patterns in the Parkinson's Disease (2012)
In the clinical praxis Gait Analysis constitutes one of the key tools for the diagnose and follow up of some pathologies. The conventional approach includes the approximation of the skeleton by the placement and detection of a set of markers, this procedure has some relevant drawbacks and can be better approached by a markerless strategy, where the dynamics of the body are estimated without the use of any artifact. The main goal of this thesis is to present some markerless approaches that allow the characterization of the human gait. For the analysis pathological gait, we focus on the Parkinson's Disease, a neurodegenerative disorder whose symptoms results in diculty to perform complex motor task among themwalking.